The power of Jamu : Kekayaan dan kearifan lokal Indonesia / Martha Tilaar, Bernard T. Widjaja ; editor Intarina Hardiman. - MARTHA TILAAR; Bernard T. Widjaja; Intarina Hardiman (Gramedia, 2014)
310 hlm. : ilus. ; 24 cm [2 eks.]